Showerhead-Assisted Chemical Vapor Deposition of Perovskite Films for Solar Cell Application. (2020) - Sanders, S.; Stümmler, D.; Gerber, J. D.; Seidel, J. H.; Simkus, G.; Heuken, M.; Vescan, A.; Kalisch, H.
Abstract: In the last years, perovskite solar cells have attracted great interest in photovoltaic (PV) research due to their possibility to become a highly efficient and low-cost alternative to silicon solar cells. Cells based on the widely used Pb-containing perovskites have reached power conversion efficiencies (PCE) of more than 20 %. One of the major hurdles for the rapid commercialization of perovskite photovoltaics is the lack of deposition tools and processes for large areas. Chemical vapor deposition (CVD) is an appealing technique because it is scalable and furthermore features superior process control and reproducibility in depositing high-purity films. In this work, we present a novel showerhead-based CVD tool to fabricate perovskite films by simultaneous delivery of precursors from the gas phase. We highlight the control of the perovskite film composition and properties by adjusting the individual precursor deposition rates. Providing the optimal supply of precursors results in stoichiometric perovskite films without any detectable residues.